THE IMPACT OF GREEN INNOVATION, MARKET ORIENTATION, AND DIGITALIZATION ON MSME PERFORMANCE IN INDONESIA - Jayanto, Imam; Rahmiyati, Nekky; Prihanto, Purwaka Hari; Parwita, Gde Bayu Surya (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study investigates the impact of green innovation, market orientation, and digitalization on the performance of micro, small, and medium enterprises (MSMEs) in Indonesia. Using a quantitative approach, data was collected from MSME owners and managers across various sectors. The findings reveal that all three factors significantly enhance MSME performance, with digitalization emerging as the most influential predictor. Furthermore, market orientation mediates the relationship between green innovation and performance, highlighting the importance of customer-centric strategies in sustainable business practices. These results underscore the necessity for MSMEs to integrate digital tools, embrace green innovations, and maintain strong market responsiveness to remain competitive. The study provides theoretical contributions by extending the resource-based view (RBV) and the technology acceptance model (TAM) in the context of MSME development. Practical implications suggest that policymakers and business leaders should facilitate digital transformation and sustainability initiatives to foster long-term MSME growth. Future research could explore longitudinal effects and industry-specific moderating variables to enhance the generalizability of these findings.